RECONSIDERING PATIENT SAFETY AT NEONATAL INTENSIVE CARE UNITS: A SYSTEMATIC REVIEW - Brendo Vitor Nogueira Sousa; Raquel Ribeiro Santana; Maiane Sousa dos Santos; Ellen Simone Vasconcelos Cipriano; Carla de Oliveira Brito; Elenilda Farias de Oliveira (Universidade Federal do Paraná, 2016)
The objective was to get to know adverse events and care practices for the purpose of patient safety at a Neonatal Intensive Care Unit. Systematic review using the following descriptors: Patient Safety; Intensive Care Units, Neonatal; Adverse events. Study developed between September 2015and February 2016. Eighty-four articles were found in three databases between 2006 and 2015. After applying the screening and eligibility criteria, nine articles were selected. The analysis of the articles revealed that adverse events take place at the Neonatal Intensive Care Units, which are attributed to different factors. The actions mentioned to prevent the adverse events were continuing education, training and an increasing number of professionals, support from management, knowledge strengthening and team commitment. In conclusion, the most noteworthy adverse events were related to medication, respiratory infections and non-programmed extubations. The main factors contributing to error were excessive workloads, lack of professionals and resources and an unfavorable work environment.